Cost‐effectiveness evaluation of the PROPPR trial transfusion protocols. Issue 5 (1st May 2020) - Callcut, Rachael A.; Simpson, Kit N.; Baraniuk, Sarah; Fox, Erin E.; Tilley, Barbara C.; Holcomb, John B.; ,
Abstract : BACKGROUND: There have been no prior investigations of the cost effectiveness of transfusion strategies for trauma resuscitation. The Pragmatic, Randomized, Optimal Platelet and Plasma Ratios (PROPPR) study was a Phase III multisite, randomized trial in 680 subjects comparing the efficacy of 1:1:1 transfusion ratios of plasma and platelets to red blood cells with the 1:1:2 ratio. We hypothesized that 1:1:1 transfusion results in an acceptable incremental cost‐effectiveness ratio, when estimated using patientsʼ age‐specific life expectancy and cost of care during the 30‐day PROPPR trial period. STUDY DESIGN AND METHODS: International Classification of Diseases, Ninth Revision codes were prospectively collected, and subjects were matched 1:2 to subjects in the Healthcare Utilization Program State Inpatient Data to estimate cost weights. We used a decision tree analysis, combined with standard costs and estimated years of expected survival to determine the cost effectiveness of the two treatments. RESULTS: The 1:1:1 group had higher overall costs for the blood products but were more likely to achieve hemostasis and decreased hemorrhagic death by 24 hours (p = 0.006). For every 100 patients treated in the 1:1:1 group, eight more achieved hemostasis than in the 1:1:2 group. At 30 days, the total hospital cost per 100 patients was 5.6 million in the 1:1:1 group compared with 5.0 million in the 1:1:2 group. For each 100 patients, the 1:1:1 group had 218.5 more years of life expectancy. This was at a cost of 2994 per year gained. CONCLUSION: The 1:1:1 transfusion ratio in severely injured hemorrhaging trauma patients is a very cost‐effective strategy for increasing hemostasis and decreasing trauma deaths.